Caracterização do fator sigma extracitoplasmático ecfL de Xanthomonas citri pv. citri : Characterization of the extracitoplasmatic sigma factor ecfL from Xanthomonas citri pv. citri - Pereira, Juliana Biar, 1991- (2019)
Orientador: Cristina Elisa Alvarez Martinez